Upaya Meningkatkan Hasil Belajar Passing Bawah Bola Voli Dengan Pendekatan Pembelajaran Massed Practice - Imistauma, Ahmad; Kusuma, Lalu Sapta Wijaya; Imran, Ali (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
The following reaserch intends for intensifying volleyball lower passing skills at 1st grade students in SMP Satu Atap 3 Pringgasela. This kind of Classroom Action Reaserch (CAR) aims to fix and increase learning quality and recover teachers to solve several learning problems at school. This reaserch uses Practice Massed Method in 2 Cycles that consists a plan, implementation, action, observation, and evaluation/reflection. The samples in this reaserchis 12 students from 1st grade. The results show that volleyball lower passusing massed practice method at 1st grade of SMP Satu Atap 3 Pringgasela increased from cycle 1 got 5 students (41.6%) passed and 7 students (58.3%) unpassed. And from cycle 2 shows 9 students (75%) passed and 3 students (25%) unpassed. According to the result can be stated an incrase occurs 33% in cycle 1 and 2.